Proposta de integração RUP + PMBOK na gerência de escopo no processo de desenvolvimento de software - Gomes, André Luís Sanson (2009)
Software organizations of development are always searching to increase the product quality of software, for that is necessary that the processes well are defined and can be controlled. However, some difficulties are found as: processes directed total toward the productive activity and with little or no management activity, bad the management of projects or absence of management, not attendance the expectation of the involved ones. These processes must allow a methodology of management of projects that describes the activities important to all to assure the quality of the project with one, including the product and the process. In this context, this research considers an integrated process using a methodology of management of projects and a process of development of software in the area of target management. Contributing so that management and productive activities are executed of integrated form and using the area of target management to determine correctly as these activities they must be developed in the project in order to produce the foreseen deliveries. Like this, the process is presented and a use example, so that it can assist the managers in the taking of decision and planning, execution and control of the projects